A human cyber-physical system for resource and information management in hospital wards - Weaver, Keegan Matthew (Stellenbosch : Stellenbosch University, 2025)
Weaver, K. M. 2025. A Human Cyber-Physical System for Resource and Information Management in Hospital Wards. Unpublished masters thesis. Stellenbosch: Stellenbosch University [online]. Available: https://scholar.sun.ac.za/items/8dc12051-f111-416f-af41-8131a3b0bdbb